Facebook, Inc. : curating moods in a newsfeed experiment - Ferguson, Kyle; Hernandez, Javier; Weber, Mark; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In 2014, the National Academy of Sciences published a study about an emotional contagion experiment that Facebook conducted on almost 700,000 of its members. Unbeknownst to test subjects, Facebook manipulated the newsfeeds certain members received and studied their reactions. This led to media coverage that called into question Facebook's ethics and corporate procedures. This case examines media and network user backlash to the experiment, and looks at Facebooks policy on behavioral studies.
Originally published: Ferguson, K., Hernandez, J., Weber, M., & ORourke, J. S. (2016). Facebook, Inc.: Curating moods in a newsfeed experiment. 16-02. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Facebook (Firm); Business ethics; Organizational behavior; Social media